Antiarrhythmic effects of newly developed propafenone derivatives - Ivković, Branka; Opačić, Dragan; Džudović, Boris; Crevar, Milkica; Gojković-Bukarica, Ljiljana (Archives of Pharmacy, 2022)
It is well known that the presence of different chemical groups in drug molecules influences their pharmacological properties. The aim of our study is to investigate whether newly synthesized derivatives of propafenone, with changes in benzyl moiety, have a different effect upon arrhythmia, compared to propafenone. 5OCl-PF and 5OF-PF are derivatives of propafenone with -Cl or –F substituent on the ortho position of the benzyl moiety. For verification of their antiarrhythmic effect, we used an in vivo rat model of aconitine-induced arrhythmia. 5OCl-PF speeded the appearance of supraventricular premature beats (SVPB) and death more than aconitine. All animals treated with 5OCl-PF developed ventricular premature beats in salvos (VPBS), bigeminies (VPBB) and paroxysmal ventricular tachycardia (PVT). 5OF-PF had a negative chronotropic effect and potentiated atrial excitability (more SVPB). It had a positive effect on the occurrence and onset time of supraventricular tachycardia, VPBS, and PVT. Based on the obtained results, it can be concluded that newly synthesized propafenone derivatives have no better antiarrhythmic effect than the parent compound. In the future, our research will be focused on the synthesis of different derivatives and examining their antiarrhythmic effects.